2002
DOI: 10.1046/j.1440-1681.2002.03779.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the angiotensin‐converting enzyme inhibitor alacepril on exercise capacity and neurohormonal factors in patients with mild‐to‐moderate heart failure

Abstract: 1. Alacepril is a long-acting, sulphydryl-containing angiotensin-converting enzyme inhibitor. Data are limited regarding the effects of alacepril on exercise tolerance in patients with chronic heart failure (CHF). The aim of the present study was to determine the effects of chronic alacepril treatment on exercise capacity and neurohormones in patients with CHF. 2. The effects of 12 weeks treatment with alacepril on clinical, echocardiographic and cardiopulmonary exercise variables were studied in 18 CHF patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…However, other studies have shown that long-term treatment with angiotensin-converting enzyme inhibitors (26), beta-blockers (27), and diuretics (28) decrease BNP levels. We cannot, therefore, exclude that initiation of such treatments might have contributed to the decreasing NT-proBNP levels, especially during the later part of the measurement period.…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies have shown that long-term treatment with angiotensin-converting enzyme inhibitors (26), beta-blockers (27), and diuretics (28) decrease BNP levels. We cannot, therefore, exclude that initiation of such treatments might have contributed to the decreasing NT-proBNP levels, especially during the later part of the measurement period.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, five such ACEIs are commercially available for veterinary use; however, these drugs have not been fully investigated through comparative studies to determine which of these drugs is more effective and advantageous in treating heart failure. For example, although alacepril is a long-acting, sulfhydryl-containing ACEI, very little information is available regarding its cardioprotective effects [9]. In the present study, we evaluated the cardioprotective effects of alacepril and compared the effects with another ACEI, enalapril, which is widely used in veterinary medicine.…”
Section: Introductionmentioning
confidence: 99%
“…Criteria such as cardiothoracic ratio and left ventricular end-diastolic diameters (124) or increases in maximal exercise capacity during the bicycle exercise stress test and improvement in NYHA class were associated with decreases in BNP concentrations during follow-up of congestive HF patients (125). However, most studies report mean natriuretic peptide changes in parallel with different criteria for the improvement of HF without showing the individual course of a patient.…”
Section: Disease Monitoring Of Heart Failurementioning
confidence: 98%